I, human : AI, automation, and the quest to reclaim what makes us unique - Chamorro-Premuzic, Tomas (Harvard Business Review Press, 2024)
It's no secret that AI is changing the way we live, work, love, and entertain ourselves. Dating apps are using AI to pick our potential partners. Retailers are using AI to predict our behavior and desires. Rogue actors are using AI to persuade us with Twitter bots and fake news. Companies are using AI to hire us-or not. This is just the beginning